CASH FLOW MANAGEMENT OF A CONSTRUCTION COMPANY DURING ECONOMIC INSTABILITY - Nurzhan Bakhadurov (Scholar Express Journals, 2025)
The article discusses the specifics of cash flow management in construction companies in the context of economic instability. It emphasizes the importance of financial planning and control during periods of rising inflation, fluctuations in prices for construction materials, and changes in lending conditions. Key risk factors, such as rising resource costs, long project implementation periods, cash gaps, and rising accounts receivable, are identified. Methods and tools for effective cash flow management, including budgeting, project financing, factoring, and digitalization of financial processes, are disclosed. Particular attention is paid to the formation of reserve funds, diversification of funding sources, implementation of stress testing, and scenario analysis. Practical recommendations are formulated aimed at increasing the sustainability of construction companies and their competitiveness in the market.
Keywords: Cash flows; construction company; economic instability